LIFE CICLE AND RATE OF NATURAL INCREASE OF G.’ ANNECTENS, N. IDAEUS Y P. PERSIMILIS (ACARINA: PHYTOSEIIDAE) - MESA-C., NOHORA CRISTINA; BELLOTII, ANTHONY C.; DUQUE, MYRIAM CRISTINA (Revista Colombiana de Entomología, 1988)
Studies on Galendromus annetens (Denmark y Muna) life cycle and natural rate in-crease were conducted under laboratory conditions at 25°C and 70±5°/o of HR and using Tetranychus urticae and Mononychellus progresivus as prey. The average development time from egg to adult tor G. annectens, N. idaeus and P. persimilis was 6,1; 4,2 and 4,8 days respectively, using T. urticae and 5,7; 4,1 and 4,0 days using M. progresivus as prey number of egg female day, for G. annectens, N. idaeus and P. persimilis was 1,5; 1,6 and 3,1 using T. urticae and 2,2; 1,9 and 3,1 using M. progresivus. The rate natural increase was 0,184, 0,252 and 0,282 using T. urticae and 0,220, 0,257 and 0,280 using M. progresivus.